Taṭwīr Mawād al-Muḥādaṡah Bi Barnāmij Microsoft Powerpoint Li Tarqiyah Qudrah aṭ-Ṭalabah `Alā Mahārah al-Kalām (Dirāsah al-Baḥṡ Wa at-Taṭwīr Bi STAI Darul Hikmah Aceh Barat) - Maulida Maulida; Azman Ismail; Moch. Fajarul Falah (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2022)
It was noted from the observations that most of the students can only memorize and understand the vocabulary, but cannot arrange it to become a sentence and cannot communicate in Arabic, the causes were the inappropriate teaching media used by the lecturers and the short time they have with the lecturer. Those things cause the students to become difficulty composing Arabic sentences and the inability to communicate with Arabic friends and lecturers. After the researcher distributed the questionnaire to the students, the researcher found that the students liked conversational material and needed learning media that facilitated students to have conversations with friends and lecturers, and they needed the development of conversational materials with learning media. Therefore, lecturers need learning media to display these lessons. Based on this phenomenon, the researchers tried to overcome the problems that occurred by developing muhadatsah lessons in improving students' speaking skills with the Microsoft PowerPoint program. The purpose of this study was to determine how the development of muhadatsah lessons in improving students' speaking skills with the Microsoft PowerPoint program and how effective the product was. The research method that the researcher used was R&D. The research instruments used by researchers to collect research data were observation, interviews, questionnaires, and tests. The results of the research that the researchers obtained were: the development of muhadatsah lessons in improving students' speaking skills with the Microsoft PowerPoint program following 10 predetermined steps, and the t-test value (t-count = 23.18) is greater than the value (t-table with a significant level 5% = 2.11 and a significant level of 1% = 2.90). Then, it shows that the null hypothesis is rejected and the alternative hypothesis is accepted, which means that the Microsoft PowerPoint program is effective in increasing students' ability to improve speaking skills in muhadatsah lessons.